Neoadjuvant chemotherapy compared with surgery alone for locally advanced cancer of the stomach and cardia: european organisation for research and treatment of cancer randomized trial 40954 - Schuhmacher, Christoph P.; Gretschel, Stephan; Lordick, Florian; Reichardt, Peter; Hohenberger, Werner; Eisenberger, Claus F.; Haag, Cornelie; Mauer, Murielle E.; Hasan, Baktiar; Welch, John; Ott, Katja; Hoelscher, Arnulf; et al. (Journal of clinical oncology, 2010)
Patients with locally advanced gastric cancer benefit from combined pre- and postoperative chemotherapy, although fewer than 50% could receive postoperative chemotherapy. We examined the value of purely preoperative chemotherapy in a phase III trial with strict preoperative staging and surgical resection guidelines. 0999 Alle Personen wegen Universitätsbibliographie Heidelberg bitte stehen lassen! HDHB/04.07.2023
Gesehen am 04.07.2023